Extracorporeal Venovenous Membrane Oxygenation in the Treatment of Respiratory Insufficiency Following Cardiac Surgery. Issue 2 (12th January 2014) - Bignami, Elena; Frati, Elena; Meroni, Roberta; Verzini, Alessandro; Pozzoli, Alberto; Benussi, Stefano; Alfieri, Ottavio
Abstract Following cardiac surgery, patients can develop acute respiratory failure. We present the case of a 66‐year‐old male successfully treated with extracorporeal venovenous membrane oxygenation (vvECMO) for acute respiratory failure postsurgery and review the literature on vvECMO in this specific setting. doi: 10.1111/jocs.12278 (J Card Surg 2014;29:270–273)